Combining transcriptomics and metabolomics to analyse the mechanism of allelopathy in Cyclachaena xanthiifolia - Zelin Yang; Xiaoling Han; Zhixiang Xing; Fumeng He; Tianshuai Qi; Xue Wang; Rao Fu; Chong Du; Xu Feng; Yingnan Wang; Qiang Yuan; Fenglan Li; et al. (BMC Plant Biology)
Abstract As a vicious invasive plant, Cyclachaena xanthiifolia has caused severe ecological disruption and significant reductions in crop yield, necessitating urgent control measures. However, the underlying mechanisms of its allelopathic invasion remain unclear, representing the primary bottleneck in current management strategies. In this study, we used metabolomic and transcriptomic analyses to evaluate the differences in allelopathy and related physiological and biochemical indices among different extract fractions of C.xanthiifolia, and to investigate how the allelopathy of C.xanthiifolia inhibits seed germination and seedling growth by altering metabolic pathways. GC-MS results identified several compounds with allelopathic potential, including fatty acids, terpenes, esters, alkanes, and aldehydes. Among them, n-butanol phase extract (NE) treatment significantly inhibited the germination and water absorption of mustard (Brassica juncea) seeds, changed the balance of the endogenous hormones abscisic acid (ABA) and gibberellins (GA) in seeds, destroyed the antioxidant enzyme system, and caused plasma membrane damage. Moreover, transcriptomic and broadly targeted metabolomic analyses showed that NE treatment interfered with primary metabolism, significantly enriched the carotenoid biosynthetic pathway, and led to a significant accumulation of ABA. The quantitative real-time PCR (qRT-PCR) results showed that the expression levels of 7 key genes involved in ABA biosynthesis and metabolic pathways were relatively high. The results showed that C.xanthiifolia may exert its allelopathic effects by disrupting the antioxidant enzyme system and interfering with primary metabolism and hormone signalling, and that the modulation of the ABA signalling pathway appears to play a key role.